Geopetrological model of formation diamond-bearing fluid-explosive breccia structures (urals type) - Lyudmila N. Sharpenok; Lyudmila I. Lukianova; Oleg V. Petrov (Литосфера, 2018)
Geopetrological model of diamond-bearing fluid-explosive breccia formations is a well-structured system of the features that are typical of several similar formations in the Cis-Ural and West Ural areas of the Perm Krai. The model reflects a number of basic common factors in these structures’ morphology, their rock composition and the conditions for their formation. Regional and local geological positions featuring diamond-bearing formations as well as the parameters common for their widespread formation areas are characterized. The necessity of mineralogical and geochemical studies of black sand, while prospecting for diamond-bearing targets is highlighted. This will help identify specific mineral associations and geochemical anomalies typical of these widespread formation areas. The description of the geological structure, which the best-studied Efimov deposit, is given in detail. The description of this deposit is used as an example of illustrating the shape of breccia bodies and their polyphase structure, as well as describing their texture and rock structure specifics. Particular attention is paid to the petrographic characteristics of all kinds of fluid-explosive breccias, which to a different extent contain clastic, protomagmatic and newly formed fluidogenic material. The paper gives the characteristics and specifics of mineral grains of various origin, many of which are abundant in gas-liquid inclusions, characterized by block extinction, while quartz possess planar elements. Brought into focus are the differences in the diamond bearing capacity of rocks belonging to different successive evolution phases of fluid breccia formations. The model considered in the paper will make it possible in the course of studies of newly discovered breccia structures with a limited number of parameters to predict their missing features and assessment criteria with respect to possible beneficial mineralization.